The effect of the chamber on kinetic results in cryopreserved bull spermatozoa. (28th August 2013) - Gloria, A.; Carluccio, A.; Contri, A.; Wegher, L.; Valorz, C.; Robbe, D.
Summary: In this study, the effect of the chamber used for the automated analysis of sperm motility by a computer‐assisted semen analysis system on sperm kinematics was evaluated, and the cause of this effect was also verified. Twenty‐three bull semen batches were thawed, and semen was diluted, aliquoted and analysed with six different chambers, (three capillary‐loaded chambers and three droplet (DR)‐loaded chambers). For each chamber type, each sample was analysed in quadruplicate, and the reliability of the analysis was tested using an intraclass correlation coefficient (ICC). Furthermore, sperm membrane integrity (MI) was evaluated, for each sample and chamber, in 12 randomly selected central and 12 edge fields. The ICC analysis showed that some parameters could have a significant variability related to the chamber. High stability of results was detected in Leja 4‐chamber slide. Furthermore, as previously reported in other studies, capillary‐loaded chambers seemed to affect the total and progressive motility and sperm velocities (average path velocity, straight line velocity and curvilinear velocity). These findings were corroborated by the evaluation of sperm MI that was significantly higher in the DR‐loaded chambers. This study confirms that the chamber used for the objective kinetic evaluation of bull‐thawed spermatozoa significantly affects the result. These differences could be present also in other species, even if the specific effect on the sperm kinematics should be verified. The Makler chamber seemed to give reliable results with negligible effects on sperm kinematics.